2002
DOI: 10.1103/physrevlett.88.205001
|View full text |Cite
|
Sign up to set email alerts
|

Radial Transport and Electron-Cyclotron-Current Drive in the TCV and DIII-D Tokamaks

Abstract: Calculation of electron-cyclotron-current drive (ECCD) with the comprehensive CQL3D Fokker-Planck code for a TCV tokamak shot gives 550 kA of driven toroidal current, in marked disagreement with the 100-kA experimental value. Published ECCD efficiencies calculated with CQL3D in the much larger, higher-confinement DIII-D tokamak are in excellent agreement with experiment. The disagreement is resolved by including in the calculations electrostatic-type radial transport at levels given by global energy confinemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 20 publications
6
66
0
Order By: Relevance
“…where D and v are fit to observed transport in tokamaks [9][10][11][12] and reversed-field pinches (RFP) [13][14][15]. By making a detailed study of ion transport in the RFX we have found a link between pinch velocity and a magnetic chaotic topology [16].…”
Section: Introductionmentioning
confidence: 99%
“…where D and v are fit to observed transport in tokamaks [9][10][11][12] and reversed-field pinches (RFP) [13][14][15]. By making a detailed study of ion transport in the RFX we have found a link between pinch velocity and a magnetic chaotic topology [16].…”
Section: Introductionmentioning
confidence: 99%
“…Applying this correction improves agreement on deposition centers between TORAY and experimental deposition centers compared with past work [3] [7].…”
Section: Correction Termsmentioning
confidence: 52%
“…"# derived from ECE data using FFT or BIS analysis to compare with ray tracing analysis of ECH [2][7], these efforts found transport to be a cause of significant broadening over that of TORAY, with even high frequency modulation producing far wider experimental profiles [3].…”
Section: Deposition Analysis Of Diii-d Datamentioning
confidence: 99%
See 1 more Smart Citation
“…At high enough power, the plasma temperature is high and the transport effects strong enough such that radial transport dominates the collisional slowing down time of the fast electrons. Our calculations [8] show that this is strongly the case for a representative full-toroidal-current-drive electron cyclotron current drive (ECCD) experiment [9] in the TCV fusion energy tokamak. Although there is little doubt as to whether plasma turbulence is responsible for the observed radial transport in excess of collisional levels [10], questions remain on the extent electrostatic (ES) or magnetic turbulence dominates [11] and also the degree of concurrence between tail electron transport and bulk plasma transport.…”
mentioning
confidence: 97%